Total assignment of the 1H and 13C NMR spectra of piperovatine. Issue 1 (1998) - Rendón Rendón, Willy Willy; Chávez Chávez, Galia Galia; Meléndez-Rodríguez Meléndez-Rodríguez, Myriam Myriam; Joseph-Nathan Joseph-Nathan, Pedro Pedro
Abstract : Total and unambiguous assignment of the 1 H NMR spectrum of piperovatine [6‒(4‒methoxyphenyl)‒ N ‒(2‒methylpropyl)‒2, 4‒hexadienamide] was carried out using conventional 1D NMR methods and spectral spin–spin simulation. Based on these data, the complete assignment of the 13 C NMR chemical shift values was made by a 13 C/ 1 H chemical shift correlation diagram and conventional considerations for the quaternary carbon atom.